A perspective on practical solar to carbon monoxide production devices with economic evaluation. Issue 1 (5th November 2019) - Chae, Sang Youn; Lee, Si Young; Han, Sung Gyu; Kim, Honggon; Ko, Jongwon; Park, Sejin; Joo, Oh-Shim; Kim, Donghwan; Kang, Yoonmook; Lee, Ung; Hwang, Yun Jeong; Min, Byoung Koun
Abstract : Solar-chemical production is one of the most promising options for producing valuable chemicals from greenhouse gases. Abstract : Solar-chemical production is one of the most promising options for producing valuable chemicals from greenhouse gases. An economically attractive and industrially applicable solar-chemical production device not only requires catalyst and/or reactor design, but also auxiliary unit process design, process integration, and optimization. Herein, we report a state-of-the-art monolithic solar-chemical production device having 8.03% solar to CO conversion efficiency and 0.77 to 31.9% CO2 one path conversion. Since the monolithic device directly couples a photovoltaic cell and a CO2 electrolyzer, the power loss due to a current converter can be avoided. According to the solar-chemical production device, a comprehensive process design accounting for CO2 to CO conversion, unreacted CO2 separation, and recycling structure is provided. The process model shows good agreement with experimental data for CO2 conversion in the electrolyzer. A process level techno-economic evaluation and a comprehensive review are also presented to highlight the current state and the economic feasibility of the developed device. Thereafter, we provide a sensitivity analysis in terms of CO2 conversion, membrane cost, solar to chemical efficiency, and current density necessary for economically profitable CO production. The equivalent CO sales cost from a 4 MW production plant is estimated to be $10.9 per kg and the corresponding carbon tax compensating for the price gap of the current market price is $6.6 per kg CO2 . The sensitivity analysis demonstrates that >80 mA cm −2 current density or 22% CO2 conversion is desirable to effectively compete with the conventional CO production process.